Goblet Cells Proliferation of Duodenum, Jejunum, and Ileum of Laying Hens Immunized with Protein of Excretory-Secretory of Ascaridia galli - Balqis, Ummu; Tiuria, Risa; Priosoeryanto, Bambang Pontjo; D, Darmawi (Jurnal Kedokteran Hewan, 2007)
This research was conducted in order to examine the goblet cells proliferation in duodenum, jejunum, and ileum of laying hens due to exposured with protein of excretory/secretory (ES) of Ascaridiagalli adult worm. Thirty heads of laying hens were divided in to two groups. The first group was treated with 4,000 infective larva (L2) of A. galli and the second group was immunized with 380g of ES andfour hours later was challenged with 4000 L2. All treatments were given orally using stainless steelcanule directly to the oesophagus. Data was taken on the 3, 6, 9, 12, and 15 days post immunization(p.i.). The goblet cells were determined by Periodic Acid Schiff (PAS) staining. The result showed that immunization was able to increased goblet cells proliferation significantly at 12 and 15 day p.i. on theduodenum, and at 9, 12, and 15 day p.i. on the jejunum, but goblet cells proliferation did notsignificantly on the ileum. From this result we suggested that ES would beneficial in the strengthen thehosts defence mechanisms in the intestinal mucosa.Keywords: Ascaridia galli, excretory/secretory, goblet cells